2011
DOI: 10.1007/s00402-011-1385-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome after Chevron–Akin double osteotomy versus isolated Chevron procedure: a prospective matched group analysis

Abstract: These findings indicate that Chevron-Akin double osteotomy is a save and practicable procedure for the treatment of mild-to-moderate hallux valgus. Superiority of combined Chevron-Akin procedure over an isolated Chevron osteotomy might be limited to distinct clinical settings, but should not be generally assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 17 publications
6
24
0
Order By: Relevance
“…We found no difference in IMA correction between the 2 techniques (7.0 and 7.3 for the Mitchell and chevron groups, respectively). Our results for correction of the IMA were comparable with those reported in current studies (2,4,5,8,27). Lechler et al (27) found a mean postoperative IMA of 8 after chevron osteotomy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found no difference in IMA correction between the 2 techniques (7.0 and 7.3 for the Mitchell and chevron groups, respectively). Our results for correction of the IMA were comparable with those reported in current studies (2,4,5,8,27). Lechler et al (27) found a mean postoperative IMA of 8 after chevron osteotomy.…”
Section: Discussionsupporting
confidence: 94%
“…Our results for correction of the IMA were comparable with those reported in current studies (2,4,5,8,27). Lechler et al (27) found a mean postoperative IMA of 8 after chevron osteotomy. In a study conducted by Radwan and Mansour (8), the mean postoperative IMA was 8.23 .…”
Section: Discussionsupporting
confidence: 94%
“…21 The authors suggested the superiority of a combined Chevron-Akin osteotomy over an isolated Chevron procedure. 22 Lechler et al 10 reported that the mean improvement of HVA in the Chevron-Akin double osteotomy group was significantly greater than that of the Chevron osteotomy group, while the mean improvement of IMA did not differ between the two groups. Our results were similar, however, another study 23 demonstrated sufficient reduction of HVA in almost all cases by the Scarf procedure 24 alone without the need for a phalangeal osteotomy.…”
Section: Discussionmentioning
confidence: 94%
“…5,7,8 Additional surgery such as distal soft tissue procedures (DSTPs), Akin osteotomy, 9 and supplementary Kirschner (K-) wire fixation are frequently combined with first metatarsal osteotomy. 10,11 However, little has been reported about the effect of these additional procedures on the outcomes and recurrence of hallux valgus after first metatarsal osteotomy.…”
mentioning
confidence: 99%
“…22 What is unclear is how this affects the tracking of the sesamoids under the MT head. The radiographic evaluation of bunion deformities is inadequate to assess first MTP joint congruity, sesamoid location, and TMT instability and should have only a very limited role in surgical planning.…”
Section: Erosion Of Cristamentioning
confidence: 99%